Base-controlled [3+3] cycloaddition of isoquinoline N-oxides with azaoxyallyl cations. Issue 68 (3rd August 2016) - An, Yuanyuan; Xia, Hongguang; Wu, Jie
Abstract : A base-controlled [3+3] cycloaddition reaction of isoquinoline N -oxides with azaoxyallyl cations is developed, leading to 1, 11 b -dihydro-[1, 2, 4]oxadiazino[3, 2- a ]isoquinolin-2(3 H )-ones and 2-(isoquinolin-1-yloxy)acetamides, respectively. This transformation proceeds through an azaoxyallyl cation generated in situ from α-bromohydroxamate. Abstract : A base-controlled [3+3] cycloaddition reaction of isoquinoline N -oxides with azaoxyallyl cations is developed. 1, 11 b -dihydro-[1, 2, 4]oxadiazino[3, 2- a ]isoquinolin-2(3 H )-ones are obtained when isoquinoline N -oxides are treated with α-halohydroxamates in the presence of sodium carbonate, while 2-(isoquinolin-1-yloxy)acetamides are unexpectedly produced when the base is changed to cesium carbonate. This transformation proceeds through an azaoxyallyl cation generated in situ from α-bromohydroxamate, and the [3+3] cycloaddition reaction is the key step for the final outcome.